PERANCANGAN KONSTRUKSI PADA SEGWAY - Alvin Soesilo; Agustinus Purna Irawan; Frans Jusuf Daywin (Jurnal Ilmiah Teknik Mesin POROS, 2017)
Abstract: Segway is the two wheeled personal transportation device which is light, strong, can balance themselves and used for short distance. On this segway design, performed modeling and construction load simulation with the help of Autodesk Inventor Professional 2012 software. On the loading simulation results, it was shown that segway’s construction have good strength, so it is safe to be driven.